Sense of Self and Sensitivity : Does Self-Assessed Professional Ethics Competence Predict Performance in a Professional Ethical Sensitivity Test Task? - Louko, Vilma (My University, 2024)
The professional ethical standards in healthcare are maintained by means of regulation, education, and assessment. For Finnish psychologists and speech and language therapists (SLTs), professional ethical conduct is guided by codes of ethics, but there is a lack of suitable instruments for assessing skills levels in professional ethics. This thesis compares the results of two methods of assessing professional ethical competence. The purpose of this study is to determine how well self-assessments of ethical sensitivity correspond to test-assessment results. The study also compares the psychologists’ and SLTs performances as measured with the two instruments and the effect of occupation and age on the assessment results. A scenario-based assessment instrument was developed for the purposes of this study. Only the ethical sensitivity test section of the PEST (Professional Ethics Scenario Test for Psychologists and Speech and Language Therapists) is used in the method comparison study. An electronic questionnaire was sent to the members of the Finnish Psychological Association and the Finnish Association of Speech and Language Therapists in September 2022. In the course of three months, 137 qualifying responses were received. The relationship between the two instruments were explored with correlation coefficients. The differences between the occupations as well as the effects of occupation and age on the assessment results were analysed using t-tests and a general linear model procedure. The results indicated that self-assessed ethical competence and performance in an ethical sensitivity test task were very weakly positively correlated, but very weak significant group-level correlations could only be found for two of the six factors comprising the self-assessment instrument, ‘Ethical motivation’ and ‘Ethical judgment’. No statistically significant differences were found in the psychologists’ and the SLTs self-assessment scores even though the SLTs scores were generally higher. Similarly, no significant differences were found in the psychologists’ and the SLTs’ test-assessed ethical sensitivity scores despite the psychologists’ average test scores being higher. On average, the results showed that the younger the participants were, the better they performed in the ethical sensitivity section of the scenario test whereas the effect of occupation on the test scores showed contrasting patterns in the psychologists’ and the SLTs’ self-assessment scores. However, no statistically significant effects of occupation or age were found. The results of this study suggest that self-assessments and test assessments of competence levels in ethical sensitivity do not produce similar results, lower self-assessments in the ‘Ethical motivation’ and ‘Ethical judgment’ sections of the PECQ (Professional Ethics Competence Questionnaire for Psychologists and Speech and Language Therapists) were associated with weaker performance in the ethical sensitivity test section. These results suggest that weaker ethical motivation and perceived deficiencies in ethical judgment skills may also reduce ethical sensitivity. Even though the analyses did not find any significant differences between the psychologists’ and the SLTs self-assessed or test-assessed competencies, there was considerable variability in the results for both professions. This implies that there may be variability in professional ethics skill levels regardless of occupation and age. Test-assessed ethical sensitivity declined with age for both professional groups. The results of this study will need to be verified with further research using larger samples. The professional ethical competence of psychologists and SLTs should be researched further in order to identify the factors which contribute to professional ethical development and to help develop education to support the achievement of these objectives.

Ammattieettisten periaatteiden toteutumista terveydenhuoltoalalla pyritään turvaamaan säännöstöjen, koulutuksen sekä arvioinnin keinoin. Suomalaisten psykologien ja puheterapeuttien kohdalla ammattieettisen työn tasoa turvaavat ammattialojen eettiset säännöstöt, mutta taitotason arviointiin soveltuvia menetelmiä ole juurikaan kehitetty. Tämä pro gradu -tutkielma vertaa kahden ammattieettisen osaamisen arviointimenetelmän tuloksia. Tutkielman tarkoituksena oli selvittää, vastaavatko itsearviomenetelmällä saadut eettisen herkkyyden arviot testimuotoisen tehtävän tuloksia. Lisäksi tutkielmassa arvioidaan psykologien ja puheterapeuttien välisiä eroja itsearviomittarin ja testimuotoisen tehtävän suorituksissa sekä selvitetään ammatin ja iän roolia keskinäisten erojen selittävinä tekijöinä. Tätä tarkoitusta varten kehitettiin ammattieettisen taidon arvioinnin skenaariotesti. Menetelmien vertailussa käytettiin skenaariotestistä ainoastaan eettistä herkkyyttä arvioivaa tehtävää. Sähköinen kysely lähetettiin syyskuussa 2022 Psykologiliiton ja Puheterapeuttiliiton kautta liittojen jäsenistölle. Kolmen kuukauden aikana vastauksia saatiin 137 kappaletta. Arviointimenetelmien yhteneväisyyksiä tutkittiin korrelaatioiden avulla. Eri ammattiryhmien välisiä eroavaisuuksia sekä ammatin ja iän vaikutuksia tuloksiin tutkittiin t-testeillä sekä yleisellä lineaarisella mallilla. Tämän tutkielman tulosten perusteella ammattieettisen osaamisen itsearviolla on hyvin heikko yhteys suoriutumiseen testimuotoisessa eettisen herkkyyden tehtävässä ja tilastollisesti merkitsevä yhteys skenaariotestin ja kuudesta osatestistä koostuvan itsearviomittarin välillä löytyi ainoastaan kahden itsearviomittarin osatestin (”Motivaatio toimia eettisesti” sekä ”Eettinen päätöksenteko”) kohdalla. Psykologien ja puheterapeuttien itsearvioiden välillä ei ollut merkitsevää eroa, vaikkakin puheterapeuttien itsearviot olivat keskimäärin korkeampia. Myöskään skenaariotestin tuloksissa ei ollut merkitsevää eroa psykologien ja puheterapeuttien välillä, mutta psykologien keskimääräiset pistemäärät olivat korkeampia. Tulosten perusteella skenaariotestin tulokset olivat keskimäärin sitä parempia, mitä nuorempia vastaajat olivat, mutta ammatin suhteen tehty vertailu paljasti eroja psykologien ja puheterapeuttien suoriutumisessa. Merkitsevää iän tai ammatin vaikutusta testituloksiin ei kuitenkaan havaittu tässä aineistossa. Tulokset antavat viitteitä siitä, ettei itsearvioinnilla saada testiarviota vastaavia tuloksia eettisen herkkyyden taitotason arvioinnissa. Tulosten perusteella itsearvion ”Motivaatio toimia eettisesti” sekä ”Eettinen päätöksenteko” -osatestien matalammilla arvioilla oli sen sijaan yhteys heikompaan suoriutumiseen eettisen herkkyyden testimuotoisessa arviossa. Tämä saattaa antaa viitteitä siitä, että heikompi eettinen motivaatio sekä eettisen päättelytaidon koetut puutteet vähentävät myös eettistä herkkyyttä. Vaikka psykologien ja puheterapeuttien itsearvioiduissa ja skenaariotestissä arvioiduissa suoriutumisessa ei ollut tutkimuksen perusteella merkitsevää eroa, molempien ammattiryhmien sisällä oli paljon vaihtelua, mikä viittaa vaihtelevaan ammattietiikan taitotasoon ammatista ja iästä riippumatta. Saatujen tulosten varmistamiseksi tulisi tehdä lisätutkimusta suuremmilla otoksilla. Ammattieettisen osaamisen arviointitutkimusta olisi hyvä tehdä myös vastaisuudessa eri ikäisten ja eri työuran vaiheissa olevien psykologeille ja puheterapeuteille, jotta pystyttäisiin tunnistamaan sen kehittymistä ja ylläpitoa edistäviä tekijöitä sekä kehittämään koulutusta näitä päämääriä tukemaan.
Keywords: Professional ethical competence, assessment methods, self-assessment, psychology, speech-language pathology, logopedics, ammattieettinen osaaminen, arviointimenetelmät, itsearvio, psykologia, logopedia